Business Opportunity Analysis in Cargo Transshipment Market Between Singapore and Batam, Currently Dominated by Singaporean Cartel - Giovani, Felix Ferdian; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2013)
Trade between Batam and Singapore are quite high as Batam is designated for export oriented industrial area. Currently shipping price is considered too high by the service users. It is also demanded to be more frequent. The high shipping price is believed to be caused by cartel among the existing shipping company owned by Singaporean. This situation creates an opportunity for the shipping industry between Batam and Singapore. StarPillar Pte. Ltd. is a Singapore based company which operates in concrete foundation pillar manufacturing. It is planning to form a joint venture with PT. Trans Buana Logistics to create a shipping company and take the existing market opportunity with the name of PT. Star Trans Logistics. Before deciding to make the investment decision they need to analyze whether transshipment business will be feasible in the emerging market opportunity or not. The market opportunity analysis is conducted by analyzing marketing feasibility and financial feasibility of the investment project. Market opportunity shows that there are needs of shipping service. With the estimated capabilities of PT, Star Trans Logistics the transshipment business is considered as marketing feasible. Financial feasibility is represented by NPV, IRR, payback period, and profitability of the index. The project yields NPV of S 3,804,017, IRR of 15.10%, payback period of 4 years 3.3 months, and profitability index of 1.49. These values show that the project is financial feasible.Â Keywords: transshipment, feasibility, cost estimation, sensitivity analysis